Effect of natural extract from waste corn meal on stabilization of natural rubber. (7th February 2021) - Promhuad, Khwanchat; Prasopdee, Thridsawan; Smitthipong, Wirasak
Abstract: Natural rubber (NR) consists of rubber and non‐rubber components. Under prolonged storage, non‐rubber components of NR promote network or gel formation and increase Mooney viscosity, a phenomenon otherwise known as the storage hardening phenomenon. Generally, NR properties can be stabilized by commercial synthetic stabilizers such as hydroxylamine sulfate, hydrazine stearate, and so forth. The objective of this study is to prepare constant viscosity (CV) NR with natural extract (NE) from waste corn meal. The effect of NE on storage hardening of NR was investigated. Several types of samples were prepared: NR without stabilizer, NR with 0.1, 0.2, 0.5, 1.0, and 2.0 phr (parts per hundred rubber) of NE. Samples were characterized immediately and after 12 weeks of storage time at room temperature. Physical and mechanical properties of all NR samples changed with time, but less with 2.0 phr NE because it inhibits network formation within NR. These results suggest NE is a natural stabilizer for preparing environmentally friendly CV natural rubber. Abstract :